Investigating The Causes Of The Construction Of Soil Dam Aghchay For An Arc - Sepehr Tatlari; Fouad Kilanehee; Mahmood Hassanlu rad (مهندسی و مدیریت ساخت)
Aghchay  Dam is the largest arched dam in the country. In the studies, five sites have been considered as pivotal options for the dam axis. Geological and geotechnical surveys along with field experiments showed that option 1 (upstream of the village of Khorvl Lower) was preferred to other options. In the first phase studies, the drainage curtain was straight-axial, but on the left bank there was a very large limestone mass slab that encountered sealing problems. On the right bank, there was an old buried stream that filled the slabs, so changes were made, and the water curtain was run smoothly. The choice of an arc-axle for the dam, while reducing the administrative costs, has also given a special blow to the dam.